Patient’s Knowledge of Basic Medication Information in Saudi Arabia - Alomi, Yousef Ahmed; Alaskari, Dima Ahmad; Almelf, Malak Mohammad; Badawi, Dima Ali; Alshihri, Abdullah Mohammad (Journal of Pharmacy Practice and Community Medicine)
Objective: To explore the Patients and Basic Knowledge of Medications in Saudi Arabia. Methods: It is a 4-months cross-sectional survey of patient and basic knowledge of medicines. The survey consisted of twopart, demographic information and second part forty-nine questions divided into four domains. It included domain 1: Primary or essential information about patient medication, domain 2: patient information about the drug-related problem, domain 3: patient information about drug-related cost and domain 4: patient’s perception about medications. Medline Plus health information and DailyMed-INH elements information from National Institute of Health United State of America were used. The 5-point Likert response scale system was used. The questions were open and closed-ended. The survey distributed through social media and at 500-bed pediatrics and maternity hospital in Asir region, at ambulatory care pharmacy. The authors did the patients interview with electronic survey documentation. The survey was made in an electronic format and it analyzed domain one Primary or necessary information about patient medication through survey monkey system. Results: The total responders were (614) patients with Saudi 564 (96.1%) and Non-Saudi was 23 (3.9%) nationalities. The gender distribution 523 (85.2%) were females and 91 (14.8%) were males. The most type of medications used was anti-diabetic and anti-hypertension medicines, Skin medications and drugs for Respiratory Diseases. The responders showed poor knowledge either they do not know or weak information about the generic name of Medicines 300 (54.8%), the trade name 246 (46.8%). While adequate knowledge both complete and incomplete information of drug strength 324 (60.9%) and dosage form of medication 377 (70.6%). The patients showed adequate knowledge about medications with both complete information and incomplete information about drug indication 456 (77.8%), how to use medications 496 (84.78%), the administration time 493 (84.71%), the potential to adhere medication 431 (73.9%) and the time to stop drugs 391 (67.1%). The majority of responders used health care providers 346 (57%), drug bulletin 341 (56.2%), Internet 221 (36.4%) and Relatives and friends 137 (22.57%) as sources of drug information. Conclusion: The finding showed indigent essential drug information knowledge. Targeting of public awareness of necessary information about their medications and patient counseling system will prevent drug misadventures and drug-related morbidity and mortality in Saudi Arabia.
Keywords: Knowledge; Ministry of Health; Saudi Arabia; Medications; Patient